The Dynamics of Authorial Forgetting: The Case of James Robertson - Walker, Robert G (Eighteenth-century life, 2025)
James Robertson (1713 – 95) was born in Dublin but spent most of his life in England. By profession a comic actor associated for two decades with the York Theatre, in 1770 he published anonymously a relatively large volume of poetry (239 pages), with the title Poems, Consisting of Tales, Fables, Epigrams, &c. &c. By Nobody. His attribution of his poetry to Nobody was playful, but, in an irony of history, it has turned out to be prophetic. Despite the relative success of this volume — it went through three additional editions in his lifetime — and despite a surprising amount of contemporary recognition both as a player and as a poet, he has now totally disappeared from literary history. I suggest how and why he lost his place in the canon and what value there is in reading his work today, especially as a signpost of the relative persistence of Augustan satire (Pope, Swift, and others) beyond the death of Pope in 1744.